Mechanism and flow process of debris avalanche in mining waste dump based on improved SPH simulation. (August 2022) - Wang, Hai-bin; Yan, Fei; Zhang, Li-wei; Zhang, Wei; Li, Xiang-ming; Wang, Shao-quan; Wang, Shuang
Highlights: A modified compression stable kernel function for SPH is constructed. An adaptive smooth length scheme for SPH is proposed to improve stability and accuracy. A fast particle search method is developed to march the changing smooth length. The evolutionary mechanism of the long-distance landslide in the dump is investigated. Abstract: In the present work, an improved smooth particle hydrodynamic (SPH) method is proposed for flow process and mechanism simulation of debris avalanche in mining waste dump. In this method, a modified stable kernel function for SPH is constructed, by which the compression stability can be easily achieved. Also, an adaptive smooth length scheme is proposed to overcome instability and inaccuracy caused by the large difference of neighboring particle numbers at different locations. Based on this theory, a fast particle search method is developed to march this changing smooth length and a modified cam-clay model is employed into SPH. Taking No. 2 waste dump in Nanfen iron mine as an example, the catastrophe scale and the impact scope are analyzed by the proposed method, and the accuracy of the proposed method is verified by field-measured data in a slippery event. The model is calibrated with the scale of damage, sliding range and flow accumulation form, especially the sliding distance. Moreover, the evolutionary mechanism of the long-distance landslide in the dump is investigated. Via parameters obtained by analogy, the sliding process and sliding speed are predicted for Heigou waste dump in Jingtieshan iron mine. Furthermore, influencing factors such as interface roughness and flow path are analyzed and the sliding influencing range and impact speed on the barrage dam are studied, which shows that the impacts on some dams exceed the design impact. Finally, based on those simulations, the prevention and mitigation countermeasures of Heigou waste dump are suggested.